Utilization and Effectiveness of Agro-industrial Digital Marketing in Malang Raya - Ida Bagus Damar Putra; A.A.A. Wulandira Sawitri Djelantik; I Made Sudarma; Ary Bakhtiar (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2024)
In the digital era, the agro-industrial sector has transitioned from conventional marketing to digital marketing. One of the agro-industry companies in Malang Raya, ALE, focuses on processing fruits and vegetables into healthy snack chips. The company engages in various digital marketing activities, including sales through e-commerce platforms such as Shopee, Tokopedia, and Lazada, and promotional efforts on social media platforms like TikTok and Instagram. This research aims to analyze (1) the utilization of digital marketing, and (2) the effectiveness of social media promotion based on engagement rates. The study employs both primary and secondary data, incorporating qualitative and quantitative forms, which are analyzed descriptively using a case study approach. Data collection methods include interviews, observation, and content analysis. The findings highlight the advantages of e-commerce channels, sales strategies like bundling and live streaming on e-commerce platforms, and storytelling and sales promotion strategies on social media. Additionally, the engagement rates on ALE's TikTok (12.71%) and Instagram (4.50%) indicate a high engagement rate level, with values exceeding the 2.72% benchmark, demonstrating the strong effectiveness of these platforms as promotional tools for the company.